A Sociolinguistic Analysis of Jargon and Fan-Terms in the Beri Cinta Waktu Fandom - Bagaskara Wijayakusuma Putera Dwipa; Byvan Quai Alkana; Pratista Shafa Brilian (Lingua Franca, 2025)
Beri Cinta Waktu is a drama series that aired on SCTV on October 16th, 2025. The series focuses on the life of Adila, who has to choose between two men as her true love: Trian and Rama. Due to its high rating, even from the first episode, Beri Cinta Waktu's popularity gradually increases, attracting a large audience. Since then, a fandom on social media has emerged, focusing on their interest in the drama series. The purpose of this study is to examine how fandom members utilize jargon and fan terms, including portmanteaus, acronyms, and terms created by fans themselves. The study will utilize a sociolinguistic theory developed by William Labov to observe language variations, slang, and fan terms in the Beri Cinta Waktu fanbase. The method used is a qualitative approach to assess the effectiveness of using jargon and terms within the fanbase, and also utilizes purposive sampling to categorize language formations. As a result, the three types of jargon are focused on being observed, including acronyms, portmanteaus, and specialized fan terms used in the Beri Cinta Waktu fandom. All will be analyzed structurally to find the contexts of the jargon. After all, it will be stated that the analysed jargons represent two separate objects: first, the representation of the objects in Beri Cinta Waktu, and second, the fandom elements themselves. All will be connected with sociolinguistic theory, and then concluded by the connection between the fandom and the relationship between the members themselves.